Rapid Evaluation of Novel Therapeutic Strategies Using a 3D Collagen-Based Tissue-Like Model - Maury, Pauline; Porcel, Erika; Mau, Adrien; Lux, François; Tillement, Olivier; Mahou, Pierre; Schanne-Klein, Marie-Claire; Lacombe, Sandrine (Frontiers in Bioengineering and Biotechnology, 2021)
2D cell cultures are commonly used to rapidly evaluate the therapeutic potential of various treatments on living cells. However, the effects of the extracellular matrix (ECM) including the 3D arrangement of cells and the complex physiology of native environment are missing, which makes these models far from in vivo conditions. 3D cell models have emerged in preclinical studies to simulate the impact of the ECM and partially bridge the gap between monolayer cultures and in vivo tissues. To date, the difficulty to handle the existing 3D models, the cost of their production and their poor reproducibility have hindered their use. Here, we present a reproducible and commercially available “3D cell collagen-based model” (3D-CCM) that allows to study the influence of the matrix on nanoagent uptake and radiation effects. The cell density in these samples is homogeneous. The oxygen concentration in the 3D-CCM is tunable, which opens the opportunity to investigate hypoxic effects. In addition, thanks to the intrinsic properties of the collagen, the second harmonic imaging microscopy may be used to probe the whole volume and visualize living cells in real-time. Thus, the architecture and composition of 3D-CCMs as well as the impact of various therapeutic strategies on cells embedded in the ECM is observed directly. Moreover, the disaggregation of the collagen matrix allows recovering of cells without damaging them. It is a major advantage that makes possible single cell analysis and quantification of treatment effects using clonogenic assay. In this work, 3D-CCMs were used to evaluate the correlative efficacies of nanodrug exposure and medical radiation on cells contained in a tumor like sample. A comparison with monolayer cell cultures was performed showing the advantageous outcome and the higher potential of 3D-CCMs. This cheap and easy to handle approach is more ethical than in vivo experiments, thus, giving a fast evaluation of cellular responses to various treatments.